Information System Design of Allianz Insurance - Lusi Herlina; Leo Benny (Jurnal Mandiri IT, 2022)
Insurance is an agreement between the insurance customer (the insured) and the insurance company (the insurer) regarding the transfer of risk from the customer to the insurance company. The risk transferred includes: the possibility of material losses that can be assessed with money experienced by the customer, as a result of the occurrence of an event that may / is not certain to occur. Accepting risk from the insured, insurance companies also have the same position where uncertainty about risk occurs. Thus, the insurance company can transfer the risk to another party, namely the reinsurance company. The insurance company pays a premium which will be cheaper than the premium charged to the insured. Of course, only a part of the sum insured is reinsured.